Sceniczność fotografii. Spektakl Album Karla Höckera Teatru Trans-Atlantyk jako teatralna adaptacja kolekcji zdjęć - Szczypiorska-Chrzanowska, Magdalena (Załącznik Kulturoznawczy, 2020)
Is photography ‘stageable’? How to translate the narrative of a photo album to a theater stage? On what levels do photos and theater meet while constructing the stage adaptation? This paper aims at answering (these and other) questions about the relation between photo images and the theater using the example of the mise-en-scene of a collection of photos (Karl Höcker’s album) in the performance Karl Höcker’s Album by Paul Bargetto and the Trans-Atlantyk Theatrical Group. Karl Höcker’s photo album is a collection of photos taken between June and December 1944 in Aussenkommando SS-Sola Hütte, a spa complex in Międzybrodzie Bialskie built for SS troops from Auschwitz, who used to spend their short holidays there. Paul Bargetto’s performance is made on the reconstruction and analysis of photos, created on several levels of relations between the photo and the performance, between the reality and the creation, the photo play and the theater play, the actors of then and the performers of now. The article tackles these relations discussing the following issues: how to translate the language of photography into the language of theater? How does photography (de)construct theater? And finally, how does the theater medium transform the ‘reality’ of the photo?